2010
DOI: 10.2147/cia.s9564
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate prescribing in the hospitalized elderly patient: Defining the problem, evaluation tools, and possible solutions

Abstract: Potentially inappropriate medication (PIM) prescribing in older adults is quite prevalent and is associated with an increased risk for adverse drug events, morbidity, and utilization of health care resources. In the acute care setting, PIM prescribing can be even more problematic due to multiple physicians and specialists who may be prescribing for a single patient as well as difficulty with medication reconciliation at transitions and limitations imposed by hospital formularies. This article highlights critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
149
0
17

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(166 citation statements)
references
References 51 publications
0
149
0
17
Order By: Relevance
“…Also, in geriatric prescribing, combinations of medicines which cause drug interactions, fixed combinations, dual therapy, and drugs with questionable therapeutic value should all be avoided (9)(10)(11).The quality of drugs prescription for the elderly may, therefore, be assessed by different indicators. In pharmacoepidemiological studies targeting hospitalized elderly, evaluation of parameters such as the use of potentially inappropriate medication (PIM) and polypharmacy is common (8,(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in geriatric prescribing, combinations of medicines which cause drug interactions, fixed combinations, dual therapy, and drugs with questionable therapeutic value should all be avoided (9)(10)(11).The quality of drugs prescription for the elderly may, therefore, be assessed by different indicators. In pharmacoepidemiological studies targeting hospitalized elderly, evaluation of parameters such as the use of potentially inappropriate medication (PIM) and polypharmacy is common (8,(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacotherapy is considered potentially inappropriate when the risks of its use outweigh its benefits (18)(19)(20).Exposure of the elderly population to this type of medication has been shown to be associated with increased morbidity and mortality, increased the frequency of health service use and higher occurrence of ADR (12,13,15,16,21,22).Studies have shown that the prescription of PIM to Brazilian elderly is commonplace in some different settings (23)(24)(25). However, the number of pharmacoepidemiological studies focusing on the Brazilian hospitalized elderly population during their hospital stay is small (26).…”
Section: Introductionmentioning
confidence: 99%
“…This last one initiates with the admission's pharmacological background, continues with the conciliation of the patient's intra-hospital regimen and with the checking of the resulting lists again when there is a transition in the treating service. There will be a definitive list of the medications that will be received by the patient after discharge, including an education intervention given to the patient and/or caregiver, and the communication of said information to the general ambulatory physician and specialists [10,12,13].…”
Section: Pharmacotherapeutic Conciliationmentioning
confidence: 99%
“…In several studies it has been quantified that the adverse effects caused by mistakes account for 19~56% of the total detected [12][13][14][15][16][17][18][19][20][21][22] Likewise, he concludes that the accidents with medication are public health concern whose magnitude cannot be foreseen yet [23].…”
mentioning
confidence: 99%
“…It is also important to separate out the general factors responsible for the high incidence of drug-related problems in older people [11][12][13][14][15][16][17], versus other factors that further modulate the rate of ADRs in the hospital setting. In regard to the former, it is common for older people to have many diseases at the same time that may be treated with a variety of different drugs, which obviously increases the complexity of the drug therapy for patients as well as the risk for adverse drug events, including undesirable drug-drug interactions.…”
Section: Introductionmentioning
confidence: 99%